Cysts of the child’s main bile duct: Cyst-jejunostomy on diverticular loop - Pérez Billi, Luis; Pallas, Antonio; Sbárbaro, Orestes; Murguia, Elida; Lattaro, Diver; Delfino, Aquiles; Chavarría, Oscar; Praderi, Raúl (Cirugía del Uruguay, 1986)
Analysis of three cases of choledocian cysts in Type 1 child, one of which was affected by the conventional triad and were treated by cyst-jejunostomy with diverticular loop. This procedure is simple and has a low rate. Evolution has been good in every case.